IMPLEMENTATION OF REDUNDANCY PROTOCOL LOAD BALANCING VIRTUAL ROUTER (VRRP) USING ROUND ROBIN ALGORITHM IN DATA SERVICES - Muhamad Amsyar; Isnawaty Isnawaty; Natalis Ransi (Informatics Engineering Department of Halu Oleo University, 2019)
Computer networks are the most important part of communication systems in our lives, without a computer network we cannot communicate with one another. For that we need to maintain the quality level of network services by minimizing the occurrence of failures in a network device, by which it is necessary to have a network device that can take over from the main device. Protokoli Virtual VR Redundancy (VRRP) is a protocol that is responsible for running the backup router functions when the master router has a fault condition. Mikrotik is a router that can implement load balancing techniques. Load balancing has four methods that can be applied, one of which is the Nth method, the Nth method is the development of the round robin algorithm. Load balancing is a technique for distributing traffic loads on two or more connection lines in a balanced manner. The system that was built using VRRP load balancing, was able to solve the problem when one ISP experienced a connection breakup. Systems that are built using the Nth load balancing method can divide the load equally from one gateway to another gateway. Based on the Quality of Service test on load balancing devices using the microtic routerboard 951Ui-2HnD, the results of the delay, packet loss and throughput values are good as well as the average values obtained in the Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) category .